Fish Gelatin From Surimi Processing By-Products: Extraction And Characterization - Bakar, Muhammad Khairulnizam Abu (2010)

(untitled)
Fish gelatin was extracted from surimi processing by-products of four different fish species, namely slender shad (Elongata ilisha), sin croaker (Johnius dussumieri), ribbon fish (Trichiurus lepturus) and threadfin bream (Nemipterus japonicus). These by-products consisted of skins, bones and scales. In the initial study, highest yield of fish gelatin was obtained from slender shad fish by-products and this species was then selected for optimization of gelatin extraction condition study. Several factors that could influence the gelatin extraction process were optimized using response surface methodology (RSM) approach.